FORMATION OF TOURISM LITERACY AMONG SCHOOLCHILDREN AS A FOUNDATION FOR ENVIRONMENTAL CULTURE - Iskandar Bohadyrovich Sharafutdinov (Modern American Journals, 2025)
This article explores the concepts of “tourism literacy” and “environmental culture” as interconnected components of school education. It presents techniques and methods for developing tourism literacy among students as a means of fostering environmentally conscious thinking. The article argues that green tourism can serve as an important resource for the environmental education of schoolchildren.
Keywords: tourism literacy, green tourism, school education, environmental culture, sustainable development.